Functionalization of Zirconium‐Based Metal–Organic Layers with Tailored Pore Environments for Heterogeneous Catalysis. Issue 41 (13th August 2020) - Qiao, Guan‐Yu; Yuan, Shuai; Pang, Jiandong; Rao, Heng; Lollar, Christina T.; Dang, Dongbin; Qin, Jun‐Sheng; Zhou, Hong‐Cai; Yu, Jihong
Abstract: Intriguing properties and functions are expected to implant into metal–organic layers (MOLs) to achieve tailored pore environments and multiple functionalities owing to the synergies among multiple components. Herein, we demonstrate a facile one‐pot synthetic strategy to incorporate multiple functionalities into stable zirconium MOLs via secondary ligand pillaring. Through the combination of Zr6 ‐BTB (BTB=benzene‐1, 3, 5‐tribenzoate) layers and diverse secondary ligands (including ditopic and tetratopic linkers), 31 MOFs with multi‐functionalities were systematically prepared. Notably, a metal–phthalocyanine fragment was successfully incorporated into this Zr‐MOL system, giving rise to an ideal platform for the selective oxidation of anthracene. The organic functionalization of two‐dimensional MOLs can generate tunable porous structures and environments, which may facilitate the excellent catalytic performance of as‐synthesized materials. Abstract : A facile one‐pot synthetic strategy was explored to incorporate multiple functionalities into stable zirconium metal–organic layers (MOLs) through the functionalization of Zr6 ‐BTB (BTB=benzene‐1, 3, 5‐tribenzoate) layers via secondary ligand pillaring. A metal–phthalocyanine fragment was successfully incorporated into this Zr‐MOL system, giving rise to an ideal platform for the selective oxidation of anthracene.